Risk Factors of Hepatitis C Virus Transmission - Maimoona Maheen , Mehak Ruqia , Sana Fatima, Maimoona Maheen , Mehak Ruqia , Sana Fatima (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Hepatitis C is not only a globally prevalent disease but also a significant cause of death. It has multiple complications ranging from Hepatocellular carcinoma to decompensated liver disease. This study was planned to determine the frequencies of various risk factors in Hepatitis C positive patients presenting to a tertiary care health facility in Rawalpindi. Material and Methods: This descriptive, cross-sectional study included 394 patients that presented to Liver Centre, Holy Family Hospital during the years 2015 to 2016. All these patients were confirmed cases of Hepatitis C. The data were collected from records of the liver center of Holy Family Hospital, Rawalpindi. Statistical Package for Social Sciences (SPSS), version 23 was used to analyze data, and descriptive statistics were calculated. All patients with any other comorbidity were excluded. Results: Of the 394 patients included in this study, 197 (50%) males and 197(50%) females with an average age of 44.48. Out of these, 143(36.3%) had a history of previous surgery, 65 (16.5%) had a blood transfusion, 165 (42.19%) had a history of dental treatment, and 189(48.0%) had a history of injections (IM and IV). Ninety-two patients (23.4%) had a history of barber shave, four patients (1%) had tattooing, and 83 patients (21.1 %) had a history of ear piercing. Fifty patients (38.2%) had a family history of Hepatitis C. Only 23 (31.2%) patients had only one risk factor, while 271 (68.7%) had more than one risk factor before a diagnosis of disease. Conclusion: The majority of the patients had more than one risk factor, with a history of injection use being the most common (intravenous and intramuscular). It was followed by the history of dental treatment, family history, and history of previous surgery. Keywords: Hepatitis C, risk factors, surgery, blood transfusion, dental treatment